(untitled) (Research, Society and Development, 2023)
Objective: to translate, adapt and validate the content of the scale for the use of technologies in school management from European Portuguese into Brazilian Portuguese. Methodology: the methodological process was oriented in the following order: i) permission request to adapt the scale; ii) translation of the scale from the European Portuguese language into the Brazilian Portuguese language; iii) adaptation by consensus of the translated content; iv) validation of the adapted content, which was performed by three judges, experts in the topic and context of the study through the Content Validity Coefficient (CVC), and v) agreement of the scale’ authors on the final version of the scale. Results: the CVC mean of the 3 expert rates, subtracted as a whole by the Standard Error (SE) of the rates’ differences was 0.98. Regarding the Concordance of the items, the CVCt value was 1.0. The Coherence of the items showed a CVCt value of 1.0. The Objectivity of the items registered a CVCt value of 1.0. In the Pertinence of the items, the CVCt value was 0.9. In the Adequacy of items content parameter, a CVCt value of 1.0 was registered. Conclusion: the objective of this study was successfully achieved considering the average of the CVC of the 3 expert evaluators was 0.98. Considering the literature indication, the closer the CVCt is to 1.0, the higher the content reliability is.